Updates on Titanium Dioxide - Bejaoui, Bochra (IntechOpen, 2023)
Titanium dioxide (TiO2) has received a lot of attention due to its inexpensive cost, benign nature, and great photocatalytic potential. TiO2 has numerous applications, including in photocatalysts, Li-ion batteries, solar cells, and medical research. However, its performance is unsatisfactory due to a variety of issues, including a wide band gap (3.01 to 3.2 eV) and quick electron-hole pair recombination (1012 to 1011 s). Many efforts have been made to improve the qualities of TiO2, such as structural and dopant changes, which expand its applications. This book focuses on the properties of TiO2-modified nanoparticles, including their synthesis, alterations, and applications.